Sensitivity simulation investigating the influence of subgrid scale orography - Guillaume Gastineau (Zenodo, 2020)
The main data used to generate the figure of the work entitled ''Alleviation of an Arctic Sea Ice Bias in a Coupled Model through Modifications in the Subgrid-scale Orographic Parameterization'' by Gastineau et al., submitted for publication. If you have question, please contact Guillaume Gastineau : guillaume.gastineau (at) locean-ipsl.upmc.fr